Oldie’s “Sherlock Holmes vs. The Martians”: Influence of Western Literature and Cinema. / “Sherlock Holmes vs. Los Marcianos” de Oldie: influencia de la literatura occidental y el cine. - ZINNATULLINA, ZULFIYA; KHABIBULLINA, LILIYA; ENYGIN, DMITRII (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT Contemporary literature is heavily influenced by postmodern consciousness, a variety of art forms, including cinematography, the internet and treating literature as a source of income. For this reason, new genres combining all previously mentioned elements are emerging. The most prominent examples are mashup and crossover. A striking example of the combination of mashup and crossover fiction is a novel by russian-speaking Ukrainian writers Henry Lion Oldie “Sherlock Holmes vs. the Martians” (2014). The title of the novel itself suggests that the main characters come from books by Arthur Conan Doyle and Herbert Wells. RESUMEN La literatura contemporánea está fuertemente influenciada por la conciencia posmoderna, una variedad de formas de arte, incluida la cinematografía, internet y el tratamiento de la literatura como una fuente de ingresos. Por esta razón, están surgiendo nuevos géneros que combinan todos los elementos mencionados anteriormente. Los ejemplos más destacados son mashup y crossover. Un ejemplo sorprendente de la combinación de mashup y crossover es una novela de los escritores ucranianos de habla rusa Henry Lion Oldie “Sherlock Holmes Vs. los marcianos” (2014). El título de la novela en sí sugiere que los personajes principales provienen de libros de Arthur Conan Doyle y Herbert Wells.